FATIGUE IN SYSTEMIC LUPUS ERYTHEMATOSUS AND OTHER AUTOIMMUNE SKIN DISEASES - Tarazi, M. (Br J Dermatol, 2018)
BACKGROUND: Fatigue is a well-established symptom in systemic lupus erythematosus (SLE), but has not been well-characterized in other skin-limited autoimmune diseases such as cutaneous lupus erythematosus (CLE), amyopathic dermatomyositis (ADM), or autoimmune blistering diseases (AIBD). OBJECTIVES: In this retrospective study, we compared fatigue in controls (n=84) to patients enrolled in prospective longitudinal databases with SLE (n=165), CLE (n=226), ADM (n=136), and AIBD (n=79). METHODS: We used the Short-Form 36 (SF-36) vitality scale to analyze median scores and percentage of patients with clinically significant fatigue (defined as a score ≤35) between experimental groups and controls. RESULTS: Median vitality scores demonstrated greater fatigue in experimental groups (SLE=35, IQR=20–55; CLE=50, IQR=30–70; ADM=50, IQR=30–65; AIBD=55, IQR=35–70) than controls (73, IQR=65–85) (p<0.05 between each experimental group vs. control). The SLE group had worse fatigue than all other groups (p<0.05 SLE vs. each group), but there was no difference between CLE (p>0.05), ADM (p>0.05), or AIBD (p>0.05). In addition, experimental groups had more clinically significant fatigue (score ≤35) (SLE, 44.2%; CLE, 25.2%; ADM, 31.6%; AIBD, 24.1%) than controls (2%) (p<0.01 between each experimental group vs. control). The SLE group had more clinically significant fatigue compared to CLE (p<0.01), however, there was no difference in clinically significant fatigue between SLE versus ADM (p=0.17) or AIBD (p=0.055). CONCLUSIONS: These findings demonstrate that patients with skin-limited autoimmune disease experience more fatigue than controls. Fatigue is an important symptom that negatively affects quality of life for patients and should be addressed by clinicians and measured in future clinical trials.